1987
DOI: 10.2307/1939214
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance, Pollinator Predictability, and Pollination Success Among Costa Rican Cloud Forest Plants

Abstract: Abstract. Cloud forest at Monteverde, Costa Rica experiences frequent natural disturbance. To determine whether species interactions vary spatially due to physical heterogeneity produced by disturbance, we examined relationships between 22 plant species and 11 nectar-feeding bird species in 14 study plots distributed among three patch types: large landslide-like gaps (hand-cleared areas along a trail), small gaps (formed by recent treefalls), and understory of closed-canopy forest.Species we describe here flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
5

Year Published

1987
1987
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 55 publications
2
30
0
5
Order By: Relevance
“…Morfologia e biologia floral -O predomínio de espécies com flores vermelhas e tubulosas (encontrado em todas as espécies) é característico de comunidades de plantas ornitófilas , 1996, Buzato et al 2000, Lopes 2002. A maioria das espécies ornitófilas no local de estudo (cerca de 75%) apresentou flores com corola curta (comprimento do tubo ≤ 25 mm) e foi visitada, principalmente, por beija-flores de bico curto (culmen externo < 25 mm sensu Feinsinger et al 1987), situação semelhante à observada por Linhart et al (1987), Feinsinger et al (1987) e Santos (2005. Dentre as cinco espécies de beija-flores registradas na comunidade estudada, Heliomaster squamosus e Phaethornis gounellei apresentam bicos longos (≥ 28 mm sensu Feinsinger et al 1987) e as demais, bicos curtos (< 25 mm), de maneira que o predomínio de espécies com corolas curtas permite acesso de néctar a todas as espécies.…”
Section: Discussionunclassified
“…Morfologia e biologia floral -O predomínio de espécies com flores vermelhas e tubulosas (encontrado em todas as espécies) é característico de comunidades de plantas ornitófilas , 1996, Buzato et al 2000, Lopes 2002. A maioria das espécies ornitófilas no local de estudo (cerca de 75%) apresentou flores com corola curta (comprimento do tubo ≤ 25 mm) e foi visitada, principalmente, por beija-flores de bico curto (culmen externo < 25 mm sensu Feinsinger et al 1987), situação semelhante à observada por Linhart et al (1987), Feinsinger et al (1987) e Santos (2005. Dentre as cinco espécies de beija-flores registradas na comunidade estudada, Heliomaster squamosus e Phaethornis gounellei apresentam bicos longos (≥ 28 mm sensu Feinsinger et al 1987) e as demais, bicos curtos (< 25 mm), de maneira que o predomínio de espécies com corolas curtas permite acesso de néctar a todas as espécies.…”
Section: Discussionunclassified
“…However, pollination studies in Monteverde, Costa Rica, have placed the local Burmeistera (including B. tenuiflora and B. cyclostigmata) in the ornithophilous syndrome corresponding to the short-billed hummingbird guild Murray et al 1987;Stratton 1989). While Feinsinger et al (1987) suggested that B. cyclostigmata may also be bat-pollinated based on its strong odor, they considered hummingbirds to be legitimate pollinators of both B. tenuiflora and B. cyclostigmata.…”
Section: Introductionmentioning
confidence: 99%
“…In a year-long field study, we evaluated joint responses of consumers and the plants they pollinate to a natural disturbance mosaic in the tropics (see also Feinsinger et al 1987;Linhart et al 1987). We chose a particularly well studied consumer group (nectar-feeding birds) whose morphology, behavior, and population ecology are especially closely linked to their food resources and whose use of those resources is easily quantified.…”
mentioning
confidence: 99%